Circulating Complement-C1q TNF-Related Protein 1 Levels Are Increased in Patients with Type 2 Diabetes and Are Associated with Insulin Sensitivity in Chinese Subjects - Pan, Xuebo; Lu, Tingting; Wu, Fan; Jin, Leigang; Zhang, Yi; Shi, Lihua; Li, Xiaokun; Lin, Zhuofeng (PloS one, 2014)
Complement-C1q TNF-related protein 1 (CTRP1), a member of the CTRP superfamily, possesses anti-inflammatory and anti-diabetic effects in mice. However, the clinical relevance of CTRP1 has been seldom explored. The current study aimed to investigate the association of circulating CTRP1 and type 2 diabetes mellitus (T2DM) in a Chinese population. Serum CTRP1 and adiponectin levels of 96 T2DM patients and 85 healthy subjects were determined by ELISA, and their associations with adiposity, glucose and lipid profiles were studied. In a subgroup of this study, the 75-g oral glucose tolerance test (OGTT) was performed in 20 healthy and 20 T2DM subjects to evaluate the relationship among serum levels of CTRP1 and adiponectin, insulin secretion and insulin sensitivity. Serum CTRP1 levels were significantly increased in patients with T2DM, compared with healthy controls (p<0.001). Similar to adiponectin, serum levels of CTRP1 were significantly correlated to several parameters involved in glucose metabolism and insulin resistance, and independently associated with fasting glucose levels (p<0.05) after BMI and gender adjustments. Furthermore, CTRP1 levels were positively correlated to insulin secretion, while negatively to insulin sensitivity, as measured by OGTT. CTRP1 is a novel adipokine associated with T2DM in humans. The paradoxical increase of serum CTRP1 levels in T2DM subjects may be due to a compensatory response to the adverse glucose and lipid metabolism, which warrants further investigation.